THE IMPLEMENTATION OF AI CHATBOTS IN INDONESIAN PUBLIC HOSPITALS: OPPORTUNITIES AND CHALLENGES - Evi Yanti; Ainol Mardhiah; Putri Tia Novita; Arista Ardilla; Fitri Hijri Khana (MEDALION JOURNAL: Medical Research, Nursing, Health and Midwife Participation, 2024)
This study investigates the use of AI chatbots in Indonesian public hospitals to enhance healthcare service. By leveraging Natural Language Processing (NLP) and Human-AI Interaction (HAI) theories, these chatbots streamline administrative tasks, alleviate patient overcrowding, and improve communication between patients and healthcare providers. The objective of this research is to find out how AI chatbots contribute to improving patient care and access to medical services in Indonesian public hospitals. A systematic review of articles published between 2020 and 2024 was conducted using the PRISMA framework, with a focus on the implementation of AI chatbots in Indonesian hospitals. The findings highlight successful applications in hospitals such as RSUD M. Yunus and Muhammadiyah Hospital Palembang, where chatbots effectively manage patient inquiries and reduce the workload of healthcare staff. Furthermore, chatbots have played a critical role during the COVID-19 pandemic by providing timely information to patients. Despite their advantages, challenges such as system integration and privacy concerns persist. This study offers valuable insights and proposes strategies to address these issues, emphasizing the potential of AI chatbots in improving healthcare efficiency and patient outcomes in Indonesian public hospitals.